Caracterización de personajes de las festividades de la mama negra, aplicadas en libretas, cuadernos y boceteros coleccionables para artistas, diseñadores e ilustradores - Tarco Taipe, Cristian Eduardo (2018)
The research project gets up from the analysis about of unknown and devaluation of the cultural identity of the popular festival Mama Negra of September and of the popular sectors to Latacunga Canton that also participate in the festivity but in the background, a fact that reflects a social order of power present in Latacunga. This project gathered information and compiled it into illustrations that were the result of a research focused on Bruno Munari's projecting methodology, succeeding in determining the needs and requirements of a small group of artists, designers and illustrators. Concluding with the generation of an adequate product of visual identity and diagramming techniques. Since it is important, because the characters of the Mama Negra related to the roots, tradition and culture of our ancestors, through the direct application of graphic design and the artistic representation of the syncretism of this festivity. Certainly, the qualitative methodology was the only one that used, allowing collecting information directly from reliable sources. The purpose of this project was to generate bases for future research, since it gathered historical information and reasons to celebrate the popular festival Mama Negra. Data that reflects the emotion of this celebration, characterizing the characters of this festivity, the same ones that will have a visual impact, with the proper handling of shapes and colors, expressing the very essence of the festival, making known the historical and cultural value that has the Latacunga city